PS-081 Accidental cytotoxic exposure of paediatric patients, relatives and healthcare staff: improving the safety of cytotoxic syringes. (24th March 2015) - Morand, K; Chouquet, T; Benoit, G
Abstract : Background: In paediatric patients with cancers, cytotoxic drugs are often prepared in syringes to reduce injection volumes. In view of the risk of nurses being exposed to cytotoxic substances, the syringes were secured with special devices from Codan laboratories. Several problems of cytotoxic leakage, involving syringes, were reported to the pharmacist. As the safety of healthcare staff and patients was evidently being compromised it was decided to systematically analyse and report every undesirable event. Purpose: To evaluate the safety problems related to the administration of cytotoxic syringes and to test a different system in order to replace the current device if needed. Material and methods: Over 6 months, we systematically interrogated the nurses who were reporting a problem and the devices involved were inspected. Each incident was reported to the manufacturer and the devices were sent back to them. Nurses also tested a new administration system from BD PhaSeal. A scoring table was used to assess the staff satisfaction on technical and safety criteria. Results: The Codan device was involved in seven incidents. Breaks were systematically observed at the junction between the tubing containing the cytotoxic and the non-return valve. The safety of nurses, patients and their relatives was then compromised. However, according to the manufacturer, the device was not faulty and our complaint was not followed up. Consequently, we decided to test the new device from BD (the PhaSeal system). 18 nurses participated, they assigned a score of 2.5/3 for safety criteria and 2.2/3 for handling criteria. This device seemed to improve the safety of patients and staff regarding cytotoxic exposure and microbiological contamination. Conclusion: Risk management is an important concern for pharmacists working in paediatric oncology units. Close collaboration with physicians and nurses allowed us to improve the safety of children and staff. References and/or acknowledgements: No conflict of interest.